Preparation process and application of wear-resistant and high-temperature-resistant cable

By using composite graphene, polysiloxane and modified rhododon soil in high-speed rail cable materials, and improving crosslinking degree through irradiation treatment, the existing cable materials are solved in high-temperature and frequent movement environments. The problem of insufficient wear resistance, heat resistance and thermal conductivity under the underdog has significantly improved the performance and service life of the cable.

CN119463339APending Publication Date: 2025-02-18GUANGZHOUZHUJIANG CABLE CO LTD

Patent Information

Application Number
CN202510013783.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The wear resistance, heat resistance and thermal conductivity of existing cable materials for high-speed rail and EMUs need to be further improved, especially in high temperature and frequent movement environments, which is prone to heat accumulation, deformation or wear, affecting service life.

Method used

Using a preparation process, by sorting the cable core and rubber strips, wrapping the polyester tape, and then melting and extruding the composite graphene, polysiloxane and modified rhododonite in a twin-screw extruder. The outer sheath is formed and the crosslinking degree is increased by irradiation treatment.

Benefits of technology

It significantly improves the mechanical strength, thermal conductivity and high temperature stability of the cable, extends the service life, and enhances the flame retardant effect, avoiding the accumulation of heat from the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463339A_ABST
    Figure CN119463339A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process and application of a wear-resistant and high-temperature-resistant cable, and belongs to the technical field of cable material processing. In order to solve the technical problem that in the prior art, the wear resistance, heat resistance and heat conduction performance of cable materials for high-speed trains need to be further improved, the preparation technology of the wear-resistant and high-temperature-resistant cable comprises the following steps that a plurality of cable cores are arranged in the length direction of a hemp rope with the hemp rope as the axis, and rubber strips are filled among the cable cores; and then a polyester tape and cable core mixture is wrapped outside the plurality of cable cores and the filling strips. The composite graphene, polysiloxane and modified magnesia are used as reinforcing materials to reinforce a polyethylene base material, so that the mechanical strength and wear resistance of the cable material are effectively improved, and the flame retardant property, heat resistance and heat-conducting property of the cable material are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable material processing, and in particular to a preparation process and application of a wear-resistant and high-temperature-resistant cable. Background Art

[0002] With the rapid development of modern industrial technology, the performance requirements for electrical cables are becoming increasingly higher, especially in harsh environments such as high temperature, frequent movement or stress, where the performance requirements for cables are relatively stringent.

[0003] Most of the power lines of existing high-speed trains are cable lines, which are key high-voltage electrical equipment. In addition, the operation and laying environment of cables in EMU trains is complex. In particular, high-speed EMUs with a speed of 350 km / h have large locomotive power and long high-speed operation time, which causes a sharp increase in local temperature, up to 150°C. The existing cables have poor thermal conductivity and heat dissipation performance, which can easily cause heat accumulation in the cables and cause deformation and damage to the cables during high current transmission. At the same time, the vibration or acceleration and deceleration process of the EMU train during operation will cause the cables to be pulled or swung. The constant stretching and friction will cause wear to the cables, especially for some cable materials with low cross-linking degree, which are more susceptible to friction and wear during use, reducing the service life of the cables. In severe cases, it will cause train suspension accidents.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of a wear-resistant and high-temperature resistant cable and its application, so as to solve the technical problem that the wear resistance, heat resistance and thermal conductivity of cable materials for high-speed railway vehicles in the prior art need to be further improved.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A preparation process of a wear-resistant and high-temperature resistant cable comprises the following steps:

[0008] S1. Arrange several cable cores along their length direction with hemp rope as the axis, fill rubber strips between the cable cores, and then wrap polyester tape around the outside of several cable cores and filling strips to form a cable core mixture;

[0009] S2, mixing low-density polyethylene, high-density polyethylene, composite graphene, polysiloxane, modified magnesia, catalyst and auxiliary additives uniformly, and then melt-extruding and coating them on the outside of the cable core mixture through a twin-screw extruder to form an outer sheath blank layer on the outside of the cable core mixture to obtain a wear-resistant and high-temperature resistant cable blank;

[0010] S3, irradiating the wear-resistant and high-temperature resistant cable blank to promote intermolecular cross-linking, forming an outer sheath outside the cable core mixture, and obtaining a wear-resistant and high-temperature resistant cable;

[0011] Further, the composite graphene is processed by the following steps:

[0012] A1. Under the protection of inert gas, add graphene oxide to the activation solution, raise the temperature of the reaction system to 80-90°C, keep the reaction for 3-5h, and post-treat to obtain activated graphene;

[0013] The synthetic reaction mechanism of activated graphene is:

[0014] During the reaction, the maleic anhydride in the activation solution undergoes a ring-opening condensation reaction with functional groups such as hydroxyl and carboxyl groups on the surface of graphene oxide, and unsaturated double bonds and carboxyl groups are grafted onto the surface of graphene oxide to prepare activated graphene.

[0015] A2. Under the protection of inert gas, activated graphene and DOPO are added to N,N-dimethylformamide and stirred. The temperature of the reaction system is raised to 140-150°C, and the reaction is kept at this temperature for 20-22 hours. Modified graphene is obtained by post-treatment.

[0016] The synthetic reaction mechanism of modified graphite is:

[0017] During the reaction, the active pH position on the DOPO molecule undergoes an addition reaction with the unsaturated double bonds on the activated graphene molecule, embedding DOPO into the activated graphene molecule to prepare modified graphene.

[0018] A3. Under the protection of inert gas, add modified graphene and 3-isocyanate propylene into N,N-dimethylformamide and stir. The temperature of the reaction system is raised to 70-80°C. The reaction is kept warm for 3-5 hours and composite graphene is obtained by post-treatment.

[0019] The synthesis reaction mechanism of composite graphene is:

[0020] During the reaction, the isocyanate group on the 3-isocyanate propylene molecule condenses with the oxygen-containing group on the modified graphene molecule, and a large number of unsaturated double bonds are modified on the modified graphene molecule to prepare composite graphene.

[0021] Furthermore, the preparation method of modified magnesite is as follows: magnesite and KH-560 are added to tetrahydrofuran solution, ultrasonically dispersed for 30-50 minutes, stirred, the temperature of the reaction system is increased to 50-60°C, sodium hydroxide solution is added to the reaction system, stirred for 60-80 minutes, and post-treated to obtain modified magnesite.

[0022] The synthetic reaction mechanism of modified magnesia is:

[0023] During the reaction, the sodium hydroxide solution provides an alkaline environment, which promotes the breaking of the siloxane bonds on the KH-560 molecules to form silanol groups that condense with the active groups on the surface of the magnesia particles, forming a KH-560 coating on the surface of the magnesia particles to prepare modified magnesia.

[0024] Furthermore, in step S2, the weight ratio of the low-density polyethylene, high-density polyethylene, composite graphene, polysiloxane, modified magnesia, initiator and auxiliary additive is 20-30:55-65:12-17:15-20:25-35:3-5:7-10, and the catalyst is composed of dibenzoyl peroxide and triallyl isocyanurate in a weight ratio of 1:2.

[0025] Furthermore, the temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 180°C, 185°C, 190°C, 190°C, 190°C, and 200°C, respectively; the spindle speed of the twin-screw extruder is 12r / min; the auxiliary additives are composed of dispersant, lubricant, plasticizer, light stabilizer, antioxidant and anti-aging agent in a weight ratio of 3:2:5:3:2:1; the dispersant is stearate, the lubricant is one or more of butyl stearate, oleamide, and ethylene bisstearamide, the plasticizer is phthalate, the light stabilizer is any one of light stabilizer 770, light stabilizer 783, light stabilizer 791, and light stabilizer 944, the antioxidant is any one of antioxidant 168, antioxidant 1010, and antioxidant 1076, and the antioxidant is any one of antioxidant AW, antioxidant DNP, and antioxidant CPPD.

[0026] Furthermore, in step S3, the irradiation treatment temperature is 110-120° C., and the irradiation dose is 180-230 Gy.

[0027] Furthermore, in step A1, the amount ratio of the graphene oxide and the activation solution is 1g:7mL, the activation solution is composed of maleic anhydride and N,N-dimethylformamide in an amount ratio of 1g:10mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, washed with anhydrous ethanol 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain activated graphene.

[0028] Furthermore, in step A2, the amount ratio of the activated graphene, DOPO and N,N-dimethylformamide is 2g:3g:15mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol three times and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C and dried to constant weight to obtain modified graphene.

[0029] Furthermore, in step A3, the amount ratio of the modified graphene, 3-isocyanate propylene and N,N-dimethylformamide is 5g:2g:50mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain composite graphene.

[0030] Further, the dosage ratio of the magnesia, KH-560, tetrahydrofuran solution and sodium hydroxide solution is 7g:2g:50mL:5mL, the tetrahydrofuran solution is composed of tetrahydrofuran and sodium dodecyl sulfate in a dosage ratio of 100mL:1g, the concentration of the sodium hydroxide solution is 2-3mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, suction filtration, the filter cake is washed with purified water until neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain modified magnesia. Further, the preparation method of polysiloxane is: tetramethyltetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane, and modified triazine are added to xylene and stirred, the temperature of the reaction system is raised to 110-120°C, a catalyst is added to the reaction system, the reaction is kept warm for 4-6h, and post-treated to obtain polysiloxane.

[0031] The synthetic reaction mechanism of polysiloxane is:

[0032] Under the action of high temperature and catalyst, tetramethyltetravinylcyclotetrasiloxane and octamethylcyclotetrasiloxane open their rings to form siloxysilicon segments with silanol activity, and at the same time, the siloxyethane bonds on the modified triazine molecules are broken to form silanol groups. Then, the silanol groups between the molecules undergo dehydration condensation to form long siloxysilicon segments with olefin double bonds and triazine modifications, thereby preparing polysiloxane.

[0033] Furthermore, the amount ratio of the tetramethyltetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane, modified triazine and catalyst is 4-6g:8-12g:2-3g:70-80mL:6-8mL, the catalyst is 50-60wt% sulfuric acid, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is reduced to room temperature, purified water is added to the reaction system, stirred for 10 minutes, allowed to stand for separation, the organic phase is washed with purified water until neutral and then dried, the organic phase is transferred to a rotary evaporator with a water bath temperature of 80-90°C, and the solvent is evaporated under reduced pressure to obtain polysiloxane.

[0034] Furthermore, the preparation method of the modified triazine is: under the protection of inert gas, 2-amino-1,3,5-triazine and 3-isocyanatepropylmethyldiethoxysilane are added to tetrahydrofuran and stirred, the temperature of the reaction system is increased to 50-60°C, the reaction is kept warm for 80-100 minutes, and post-processed to obtain the modified triazine.

[0035] The synthetic reaction formula of modified triazine is:

[0036]

[0037] The synthetic reaction mechanism of modified triazine is:

[0038] Under the protection of inert gas, the amino group on the 2-amino-1,3,5-triazine molecule undergoes a condensation reaction with the isocyanate group on the 3-isocyanatepropylmethyldiethoxysilane molecule, and the methyldiethoxysilane is modified on the triazine molecule to prepare a modified triazine;

[0039] The mass spectrometry data of modified triazine are: m / z: 313.1770 (100.0%), 314.1804 (13.0%),

[0040] 314.1716(5.1%),315.1749(3.3%),314.1751(1.8%).

[0041] Furthermore, the usage ratio of the 2-amino-1,3,5-triazine and 3-isocyanatopropylmethyldiethoxysilane is 1 mol:1 mol, the usage ratio of the 2-amino-1,3,5-triazine and tetrahydrofuran is 1 g:8 mL, and the post-treatment comprises: after the reaction is completed, distilling off the solvent under reduced pressure to obtain a modified triazine.

[0042] The invention discloses an application of a wear-resistant and high-temperature resistant cable, wherein the wear-resistant and high-temperature resistant cable prepared according to a preparation process of the wear-resistant and high-temperature resistant cable is applied to the power transmission of a motor vehicle group.

[0043] The present invention has the following beneficial effects:

[0044] 1. The wear-resistant and high-temperature resistant cable of the present invention uses a combination of low-density polyethylene and high-density polyethylene as basic materials, and uses composite graphene, polysiloxane, and modified magnesia as reinforcing materials to reinforce the base material. After the components are cross-linked by a catalyst, the cross-linking and bonding between the components are promoted under high-temperature radiation to improve the cross-linking degree of the sheath layer material. When preparing the composite graphene, the composite graphene is prepared by modifying DOPO and a large number of unsaturated double bonds on the graphene oxide molecules, so that the composite graphene can be evenly dispersed in the polyethylene base material. Graphene itself has good thermal conductivity and mechanical strength. It is evenly dispersed in the polyethylene base material, which can effectively improve the mechanical strength and thermal conductivity of the cable material and avoid heat accumulation in the material. Polysiloxane and modified magnesia have high stability in a high temperature environment, which can effectively improve the structural stability of the cable material in a high temperature environment. The highly cross-linked network structure further enhances the high temperature resistance of the cable material.

[0045] 2. The wear-resistant and high-temperature resistant cable of the present invention is modified with triazine and unsaturated double bonds on the polysiloxane chain segment. During the high-temperature irradiation crosslinking process, the composite graphene particles and the unsaturated double bonds modified on the polysiloxane chain segment are cross-linked with the polyolefin molecular chain segment to improve the crosslinking degree of the material. The polysiloxane chain segment itself has good thermal stability, which cooperates with the composite graphene. The thermal conductivity of the graphene and the high-temperature stability of the polysiloxane complement each other, and the high-temperature resistance of the cable is jointly improved. In addition, the triazine modified on the polysiloxane chain segment and the composite graphene Graphene and magnesia cooperate with each other to construct a synergistic flame retardant system on the outer sheath layer of the cable to enhance the flame retardant effect of the cable material. During the cable molding process, by optimizing the composition of the catalyst, the functional groups in the molecular structure of triallyl isocyanurate can react with the free radicals in the polyolefin to promote the formation of a chain reaction, thereby generating a three-dimensional network macromolecular structure. In addition, under high temperature conditions, while accelerating the decomposition of dibenzoyl peroxide, the amount of free radicals generated is increased, which is more conducive to the cross-linking reaction and increases the degree of cross-linking of the cable material.

[0046] 3. The wear-resistant and high-temperature resistant cable of the present invention promotes the uniform dispersion of magnesia by adding sodium dodecyl sulfate to a tetrahydrofuran solution to form fine particles, so that KH-560 can form a uniform coating modification on the outside of the magnesia particles. The epoxy groups on the KH-560 molecules modified on the surface of the modified magnesia undergo ring-opening condensation with oxygen-containing groups under high temperature to form chemical bonds, thereby improving the dispersibility of the modified magnesia in the polyolefin substrate. Magnesia itself is an inorganic metal mineral with good thermal conductivity, which can further enhance the thermal conductivity of the material, thereby quickly conducting heat out, preventing local overheating, and improving the high-temperature stability of the cable material during high-current transmission. In addition, the magnesia has good stability in a high-temperature environment and can be used as a filler to provide support for the material, thereby improving the mechanical strength and wear resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 It is a schematic diagram of the three-dimensional structure of the wear-resistant and high-temperature resistant cable of the present invention;

[0049] Figure 2 It is a schematic diagram of the cross-sectional structure of the wear-resistant and high-temperature-resistant cable of the present invention.

[0050] In the figure: 100, hemp rope; 200, cable core; 300, rubber strip; 400, polyester tape; 500, outer sheath. DETAILED DESCRIPTION

[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The rubber strip in this application is flame retardant rubber; low-density polyethylene: grade M2720A, melt flow rate is 18.0-22.0g / 10min; high-density polyethylene: grade DFDA-5440 NT, melt flow rate is 0.9g / 10min, tensile strength is 16.5MPa, elongation (break) is 350%.

[0053] Example 1

[0054] This embodiment provides a preparation process of a wear-resistant and high-temperature resistant cable, comprising the following steps:

[0055] S1. Preparation of composite graphene

[0056] Under nitrogen protection, maleic anhydride and N,N-dimethylformamide were mixed uniformly at a ratio of 1 g:10 mL to obtain an activation solution;

[0057] Weigh: 10 g of graphene oxide and 70 mL of activation solution are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 80°C and kept warm for 3 hours. The temperature of the three-necked flask is lowered to room temperature, filtered, washed with anhydrous ethanol three times and then dried. The filter cake is transferred to a drying oven at a temperature of 60°C and dried to constant weight to obtain activated graphene;

[0058] Weigh: 60 g of activated graphene, 90 g of DOPO, and 450 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 140°C, keep the temperature for reaction for 20 hours, lower the temperature of the reaction system to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then drain, transfer the filter cake to a drying oven at a temperature of 60°C, and dry to constant weight to obtain modified graphene;

[0059] Weigh: 50 g of modified graphene, 20 g of 3-isocyanate propylene, and 500 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 70°C, keep warm for 3 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 60°C, and dry it to constant weight to obtain composite graphene.

[0060] S2. Preparation of polysiloxane

[0061] Under the protection of inert gas, weigh: 96.1 g of 2-amino-1,3,5-triazine, 217.3 g of 3-isocyanatopropylmethyldiethoxysilane, and 768.8 mL of tetrahydrofuran, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 50° C., keep the temperature for reaction for 80 min, keep the temperature of the three-necked flask at 50° C., and evaporate the solvent under reduced pressure to obtain a modified triazine;

[0062] Weigh: 40 g of tetramethyltetravinylcyclotetrasiloxane, 80 g of octamethylcyclotetrasiloxane, 20 g of modified triazine, and 700 mL of xylene, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 110° C., add 60 mL of 50 wt % sulfuric acid into the three-necked flask, keep warm and react for 4 hours, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the reaction system, stir for 10 minutes, stand and separate the liquids, wash the organic phase with purified water until it is neutral and then dry, transfer the organic phase to a rotary evaporator with a water bath temperature of 80° C., and evaporate the solvent under reduced pressure to obtain polysiloxane.

[0063] S3. Preparation of modified magnesia

[0064] Tetrahydrofuran and sodium dodecyl sulfate were mixed uniformly at a ratio of 100 mL:1 g to obtain a tetrahydrofuran solution for later use;

[0065] Weigh: 70g of magnesite, 20g of KH-560, and 500mL of tetrahydrofuran solution are added to a three-necked flask, and ultrasonically dispersed for 30min. The three-necked flask is fixed on an iron stand with a mechanical stirrer for stirring. The temperature of the three-necked flask is raised to 50°C, and 50mL of 2mol / L sodium hydroxide solution is added to the reaction system. The mixture is stirred for 60min at this temperature. The temperature of the three-necked flask is lowered to room temperature, and the mixture is filtered. The filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain modified magnesite.

[0066] S4. Preparation of cable core mixture

[0067] A plurality of cable cores 200 are arranged along the length direction with the hemp rope 100 as the axis, rubber strips 300 are filled between the cable cores, and then a polyester tape 400 is wrapped around the outside of the plurality of cable cores and the filling strips to form a cable core mixture.

[0068] S5. Preparation of wear-resistant and high-temperature resistant cables

[0069] Dibenzoyl peroxide and triallyl isocyanurate are mixed uniformly in a weight ratio of 1:2 to obtain a catalyst for later use;

[0070] Sodium stearate, butyl stearate, dibutyl phthalate, light stabilizer 770, antioxidant 168 and antioxidant AW are uniformly mixed in a weight ratio of 3:2:5:3:2:1 to obtain an auxiliary additive for standby use;

[0071] Weigh by weight: 20 parts of low-density polyethylene, 55 parts of high-density polyethylene, 12 parts of composite graphene, 15 parts of polysiloxane, 25 parts of modified magnesia, 3 parts of catalyst and 7 parts of auxiliary additives, mix and add into a twin-screw extruder, the temperatures of 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 180°C, 185°C, 190°C, 190°C, 190°C, 200°C, the main shaft speed of the twin-screw extruder is 12r / min, and the mixture is melt-extruded and coated on the outside of the cable core mixture through the twin-screw extruder to form an outer sheath blank layer on the outside of the cable core mixture to obtain a wear-resistant and high-temperature resistant cable blank;

[0072] The wear-resistant and high-temperature resistant cable blank is placed in an irradiation box at a temperature of 110°C for irradiation cross-linking treatment, and then cooled to room temperature to form an outer sheath 500 outside the cable core mixture to obtain a wear-resistant and high-temperature resistant cable, wherein the irradiation dose is 180Gy.

[0073] Example 2

[0074] This embodiment provides a preparation process of a wear-resistant and high-temperature resistant cable, comprising the following steps:

[0075] S1. Preparation of composite graphene

[0076] Under nitrogen protection, maleic anhydride and N,N-dimethylformamide were mixed uniformly at a ratio of 1 g:10 mL to obtain an activation solution;

[0077] Weigh: 10 g of graphene oxide and 70 mL of activation solution are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 85°C and kept warm for 4 hours. The temperature of the three-necked flask is lowered to room temperature, filtered, washed with anhydrous ethanol three times and then dried. The filter cake is transferred to a drying oven at a temperature of 65°C and dried to constant weight to obtain activated graphene;

[0078] Weigh: 60 g of activated graphene, 90 g of DOPO, and 450 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 145°C, keep the temperature for 21 hours, lower the temperature of the reaction system to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and dry to constant weight to obtain modified graphene;

[0079] Weigh: 50 g of modified graphene, 20 g of 3-isocyanate propylene, and 500 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 75°C, keep warm for 4 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 65°C, and dry it to constant weight to obtain composite graphene.

[0080] S2. Preparation of polysiloxane

[0081] Under the protection of inert gas, weigh: 96.1 g of 2-amino-1,3,5-triazine, 217.3 g of 3-isocyanatopropylmethyldiethoxysilane, and 768.8 mL of tetrahydrofuran, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 55° C., keep the temperature for 90 min, keep the temperature of the three-necked flask at 55° C., and evaporate the solvent under reduced pressure to obtain a modified triazine;

[0082] Weigh: 50 g of tetramethyltetravinylcyclotetrasiloxane, 100 g of octamethylcyclotetrasiloxane, 25 g of modified triazine, and 750 mL of xylene, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 115° C., add 70 mL of 55 wt % sulfuric acid into the three-necked flask, keep warm and react for 5 h, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the reaction system, stir for 10 min, stand and separate, wash the organic phase with purified water until neutral and then dry, transfer the organic phase to a rotary evaporator with a water bath temperature of 85° C., and evaporate the solvent under reduced pressure to obtain polysiloxane.

[0083] S3. Preparation of modified magnesia

[0084] Tetrahydrofuran and sodium dodecyl sulfate were mixed uniformly at a ratio of 100 mL:1 g to obtain a tetrahydrofuran solution for later use;

[0085] Weigh: 70g of magnesite, 20g of KH-560, and 500mL of tetrahydrofuran solution are added to a three-necked flask, and ultrasonically dispersed for 40min. The three-necked flask is fixed on an iron stand with a mechanical stirrer for stirring. The temperature of the three-necked flask is raised to 55°C, and 50mL of 2.5mol / L sodium hydroxide solution is added to the reaction system. The mixture is stirred for 70min at this temperature. The temperature of the three-necked flask is lowered to room temperature, and the mixture is filtered. The filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 65°C and vacuum dried to constant weight to obtain modified magnesite.

[0086] S4. Preparation of cable core mixture

[0087] A plurality of cable cores 200 are arranged along the length direction with the hemp rope 100 as the axis, rubber strips 300 are filled between the cable cores, and then a polyester tape 400 is wrapped around the outside of the plurality of cable cores and the filling strips to form a cable core mixture.

[0088] S5. Preparation of wear-resistant and high-temperature resistant cables

[0089] Dibenzoyl peroxide and triallyl isocyanurate are mixed uniformly in a weight ratio of 1:2 to obtain a catalyst for later use;

[0090] Mix zinc stearate, oleamide, dimethyl phthalate, light stabilizer 783, antioxidant 1010 and antioxidant DNP in a weight ratio of 3:2:5:3:2:1 to obtain an auxiliary additive for later use;

[0091] Weigh by weight: 25 parts of low-density polyethylene, 60 parts of high-density polyethylene, 15 parts of composite graphene, 17 parts of polysiloxane, 30 parts of modified magnesia, 4 parts of catalyst and 8.5 parts of auxiliary additives, mix and add into a twin-screw extruder, the temperatures of 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 180°C, 185°C, 190°C, 190°C, 190°C, 200°C, the main shaft speed of the twin-screw extruder is 12r / min, and the mixture is melt-extruded and coated on the outside of the cable core mixture through the twin-screw extruder to form an outer sheath blank layer on the outside of the cable core mixture to obtain a wear-resistant and high-temperature resistant cable blank;

[0092] The wear-resistant and high-temperature resistant cable blank is placed in an irradiation box at a temperature of 115°C for irradiation cross-linking treatment, and then cooled to room temperature to form an outer sheath 500 outside the cable core mixture to obtain a wear-resistant and high-temperature resistant cable, wherein the irradiation dose is 205Gy.

[0093] Example 3

[0094] This embodiment provides a preparation process of a wear-resistant and high-temperature resistant cable, comprising the following steps:

[0095] S1. Preparation of composite graphene

[0096] Under nitrogen protection, maleic anhydride and N,N-dimethylformamide were mixed uniformly at a ratio of 1 g:10 mL to obtain an activation solution;

[0097] Weigh: 10 g of graphene oxide and 70 mL of activation solution are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 90°C and kept warm for 5 hours. The temperature of the three-necked flask is lowered to room temperature, filtered, washed with anhydrous ethanol three times and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and dried to constant weight to obtain activated graphene;

[0098] Weigh: 60 g of activated graphene, 90 g of DOPO, and 450 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 150°C, keep the temperature for reaction for 22 hours, lower the temperature of the reaction system to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and dry to constant weight to obtain modified graphene;

[0099] Weigh: 50 g of modified graphene, 20 g of 3-isocyanate propylene, and 500 mL of N,N-dimethylformamide, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 80°C, keep warm for 5 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with anhydrous ethanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 70°C, and dry it to constant weight to obtain composite graphene.

[0100] S2. Preparation of polysiloxane

[0101] Under the protection of inert gas, weigh: 96.1 g of 2-amino-1,3,5-triazine, 217.3 g of 3-isocyanatopropylmethyldiethoxysilane, and 768.8 mL of tetrahydrofuran, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 60°C, keep the temperature for 100 min, keep the temperature of the three-necked flask at 60°C, and evaporate the solvent under reduced pressure to obtain a modified triazine;

[0102] Weigh: 60 g of tetramethyltetravinylcyclotetrasiloxane, 120 g of octamethylcyclotetrasiloxane, 30 g of modified triazine, and 800 mL of xylene, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 120° C., add 80 mL of 60 wt % sulfuric acid into the three-necked flask, keep warm and react for 6 hours, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the reaction system, stir for 10 minutes, stand and separate the liquids, wash the organic phase with purified water until neutral and then dry it, transfer the organic phase to a rotary evaporator with a water bath temperature of 90° C., and evaporate the solvent under reduced pressure to obtain polysiloxane.

[0103] S3. Preparation of modified magnesia

[0104] Tetrahydrofuran and sodium dodecyl sulfate were mixed uniformly at a ratio of 100 mL:1 g to obtain a tetrahydrofuran solution for later use;

[0105] Weigh: 70g of magnesite, 20g of KH-560, and 500mL of tetrahydrofuran solution are added to a three-necked flask, and ultrasonic dispersion is performed for 50min. The three-necked flask is fixed on an iron stand with a mechanical stirrer for stirring. The temperature of the three-necked flask is raised to 60°C, and 50mL of 3mol / L sodium hydroxide solution is added to the reaction system. The mixture is stirred for 80min at this temperature. The temperature of the three-necked flask is lowered to room temperature, and the mixture is filtered. The filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain modified magnesite.

[0106] S4. Preparation of cable core mixture

[0107] A plurality of cable cores 200 are arranged along the length direction with the hemp rope 100 as the axis, rubber strips 300 are filled between the cable cores, and then a polyester tape 400 is wrapped around the outside of the plurality of cable cores and the filling strips to form a cable core mixture.

[0108] S5. Preparation of wear-resistant and high-temperature resistant cables

[0109] Dibenzoyl peroxide and triallyl isocyanurate are mixed uniformly in a weight ratio of 1:2 to obtain a catalyst for later use;

[0110] Calcium stearate, ethylene bisstearamide, diisooctyl phthalate, light stabilizer 791, antioxidant 1076 and antioxidant CPPD are uniformly mixed in a weight ratio of 3:2:5:3:2:1 to obtain an auxiliary additive for standby use;

[0111] Weigh by weight: 30 parts of low-density polyethylene, 65 parts of high-density polyethylene, 17 parts of composite graphene, 20 parts of polysiloxane, 35 parts of modified magnesia, 5 parts of catalyst and 10 parts of auxiliary additives, mix and add into a twin-screw extruder, the temperatures of 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 180°C, 185°C, 190°C, 190°C, 190°C, 200°C, the main shaft speed of the twin-screw extruder is 12r / min, and the mixture is melt-extruded and coated on the outside of the cable core mixture through the twin-screw extruder to form an outer sheath blank layer on the outside of the cable core mixture to obtain a wear-resistant and high-temperature resistant cable blank;

[0112] The wear-resistant and high-temperature resistant cable blank is placed in an irradiation box at a temperature of 120°C for irradiation cross-linking treatment, and then cooled to room temperature to form an outer sheath 500 outside the cable core mixture to obtain a wear-resistant and high-temperature resistant cable, wherein the irradiation dose is 230Gy.

[0113] Comparative Example 1

[0114] The difference between this comparative example and Example 3 is that the composite graphene in step S5 is replaced by the modified graphene in step S1.

[0115] Comparative Example 2

[0116] The difference between this comparative example and Example 3 is that the composite graphene in step S5 is replaced by graphene oxide in step S1.

[0117] Comparative Example 3

[0118] The difference between this comparative example and Example 3 is that, in step S2, when preparing polysiloxane, no modified triazine is added.

[0119] Comparative Example 4

[0120] The difference between this comparative example and Example 3 is that the modified magnesite in step S5 is replaced by magnesite in step S3.

[0121] Comparative Example 5

[0122] The difference between this comparative example and Example 3 is that no dibenzoyl peroxide is added to the catalyst in step S5.

[0123] Performance Testing:

[0124] The tensile strength, elongation at break and thermal shrinkage of the wear-resistant and high-temperature resistant cable samples prepared in Examples 1-3 and Comparative Examples 1-5 were measured with reference to Standard XF 306.1-2007 "Classification and Requirements for Flame-retardant and Fire-resistant Cables Plastic Insulated Flame-retardant and Fire-resistant Cables Part 1: Flame-retardant Cables";

[0125] The thermal conductivity of the wear-resistant and high-temperature resistant cable samples prepared in Examples 1-3 and Comparative Examples 1-5 was determined with reference to the standard GB / T 5990-2021 "Test method for thermal conductivity, specific heat capacity and thermal diffusion coefficient of refractory materials (hot wire method)";

[0126] The number of cycles of the wear-resistant and high-temperature resistant cable samples prepared in Examples 1-3 and Comparative Examples 1-5 when the blade wears through the sheath layer was determined with reference to the standard GB / T 17737.324-2018 "Coaxial Communication Cable Part 1-324: Mechanical Test Method Cable Abrasion Resistance Test";

[0127] The combustion performance grades of the wear-resistant and high-temperature resistant cable samples prepared in Examples 1-3 and Comparative Examples 1-5 were determined with reference to the standard GB 31247-2014 "Combustion Performance Classification of Electrical Cables and Optical Cables";

[0128] The specific test results are shown in Table 1 below.

[0129] Table 1-Performance test data of the sample

[0130] Project Category Tensile strength / MPa Elongation at break / % Thermal shrinkage / % Cycle times / times Combustion performance grade / level <![CDATA[Thermal conductivity / W·(m·K) -1 > Example 1 20.1 225.5 0.13 1530 B1 1.26 Example 2 20.5 226.5 0.12 1550 B1 1.31 Example 3 20.4 225.0 0.13 1545 B1 1.28 Comparative Example 1 17.5 186.5 0.18 1365 B1 1.22 Comparative Example 2 16.8 175.5 0.19 1320 B2 1.16 Comparative Example 3 20.2 220.5 0.16 1545 B2 1.19 Comparative Example 4 18.7 176.9 0.24 1385 B1 1.24 Comparative Example 5 19.2 198.5 0.18 1355 B1 1.23

[0131] Data Analysis:

[0132] Comparing and analyzing the data in Table 1 above, the wear-resistant and high-temperature resistant cable prepared by the present invention has a tensile strength of 20.5 MPa, an elongation at break of 226.5%, a thermal shrinkage rate reduced to 0.12%, a wear-resistant cycle number of 1550 times, a combustion performance level of B1, and a thermal conductivity of 1.31 W·(m·K). -1 , all performance test data are better than those of the control example, indicating that the present invention, by using composite graphene, polysiloxane and modified magnesia as reinforcing materials to reinforce the polyethylene base material, not only effectively improves the mechanical strength and wear resistance of the cable material, but also improves the flame retardancy, heat resistance and thermal conductivity of the cable material.

[0133] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0134] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0135] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing a wear-resistant and high-temperature resistant cable, characterized in that: The following steps are involved: S1. Arrange and arrange a plurality of cable cores (200) along their length direction with the hemp rope (100) as the axis, fill rubber strips (300) between the cable cores, and then wrap a polyester tape (400) around the outside of the plurality of cable cores and the filling strips to form a cable core mixture; S2, mixing low-density polyethylene, high-density polyethylene, composite graphene, polysiloxane, modified magnesia, catalyst and auxiliary additives uniformly, and then melt-extruding and coating them on the outside of the cable core mixture through a twin-screw extruder to form an outer sheath blank layer on the outside of the cable core mixture to obtain a wear-resistant and high-temperature resistant cable blank; S3, irradiating the wear-resistant and high-temperature resistant cable blank to promote molecular cross-linking, forming an outer sheath (500) outside the cable core mixture, and obtaining a wear-resistant and high-temperature resistant cable; Composite graphene is processed by the following steps: A1. Under the protection of inert gas, add graphene oxide to the activation solution, raise the temperature of the reaction system to 80-90°C, keep the reaction for 3-5h, and post-treat to obtain activated graphene; A2. Under the protection of inert gas, activated graphene and DOPO are added to N,N-dimethylformamide and stirred. The temperature of the reaction system is raised to 140-150°C, and the reaction is kept at this temperature for 20-22 hours. Modified graphene is obtained by post-treatment. A3. Under the protection of inert gas, the modified graphene and 3-isocyanate propylene are added to N,N-dimethylformamide and stirred. The temperature of the reaction system is raised to 70-80°C, and the reaction is kept warm for 3-5 hours. Composite graphene is obtained by post-treatment; The preparation method of modified magnesite is as follows: magnesite and KH-560 are added to tetrahydrofuran solution, ultrasonically dispersed for 30-50 minutes, stirred, the temperature of the reaction system is increased to 50-60°C, sodium hydroxide solution is added to the reaction system, stirred for 60-80 minutes, and post-processed to obtain modified magnesite.

2. The preparation process of a wear-resistant and high-temperature resistant cable according to claim 1, characterized in that: In step S2, the weight ratio of the low-density polyethylene, high-density polyethylene, composite graphene, polysiloxane, modified magnesia, initiator and auxiliary additives is 20-30:55-65:12-17:15-20:25-35:3-5:7-10, and the catalyst is composed of dibenzoyl peroxide and triallyl isocyanurate in a weight ratio of 1:2; in step S3, the irradiation treatment temperature is 110-120°C, and the irradiation dose is 180-230Gy.

3. The preparation process of a wear-resistant and high-temperature resistant cable according to claim 1, characterized in that: In step A1, the amount ratio of the graphene oxide and the activation solution is 1g:7mL, and the activation solution is composed of maleic anhydride and N,N-dimethylformamide in an amount ratio of 1g:10mL; in step A2, the amount ratio of the activated graphene, DOPO and N,N-dimethylformamide is 2g:3g:15mL; in step A3, the amount ratio of the modified graphene, 3-isocyanate propylene and N,N-dimethylformamide is 5g:2g:50mL.

4. The preparation process of a wear-resistant and high-temperature resistant cable according to claim 1, characterized in that: The dosage ratio of the magnesite, KH-560, tetrahydrofuran solution and sodium hydroxide solution is 7g:2g:50mL:5mL, the tetrahydrofuran solution is composed of tetrahydrofuran and sodium dodecyl sulfate in a dosage ratio of 100mL:1g, and the concentration of the sodium hydroxide solution is 2-3mol / L.

5. The preparation process of a wear-resistant and high-temperature resistant cable according to claim 1, characterized in that: The preparation method of polysiloxane is as follows: tetramethyltetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane and modified triazine are added to xylene and stirred, the temperature of the reaction system is increased to 110-120°C, a catalyst is added to the reaction system, the reaction is kept warm for 4-6 hours, and post-processed to obtain polysiloxane.

6. The process for preparing a wear-resistant and high-temperature-resistant cable according to claim 5, characterized in that: The usage ratio of tetramethyltetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane, modified triazine and catalyst is 4-6g:8-12g:2-3g:70-80mL:6-8mL, and the catalyst is 50-60wt% sulfuric acid.

7. The process for preparing a wear-resistant and high-temperature-resistant cable according to claim 5, characterized in that: The preparation method of the modified triazine is as follows: under the protection of inert gas, 2-amino-1,3,5-triazine and 3-isocyanate propyl methyl diethoxy silane are added into tetrahydrofuran and stirred, the temperature of the reaction system is increased to 50-60°C, the reaction is kept warm for 80-100 minutes, and post-processed to obtain the modified triazine, wherein the amount ratio of 2-amino-1,3,5-triazine and 3-isocyanate propyl methyl diethoxy silane is 1 mol:1 mol.

8. An application of a wear-resistant and high-temperature resistant cable, characterized in that: The wear-resistant and high-temperature resistant cable prepared by the preparation process of the wear-resistant and high-temperature resistant cable described in any one of claims 1 to 7 is applied to power transmission of EMUs.

Citation Information

Patent Citations

  • Crosslinked polyethylene insulated halogen-free low-smoke flame-retardant B1-level power cable

    CN113851266A

  • Manufacturing method of novel halogen-free low-smoke flame-retardant photovoltaic cable

    CN114864195A

Cited By

  • Heavy-current copper core conductor polypropylene insulation medium-voltage power cable

    CN120932967A

  • A high current copper core conductor polypropylene insulated medium voltage power cable

    CN120932967B